STRATEGI PENGUATAN ORGANISASI PEREMPUAN DALAM PENGURANGAN RISIKO BENCANA DI KOTA BANDA ACEH - Sherly Marlina; Indra .; Agussabti . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The research is about The Strategies for Strengthening Women's Organizations in Disaster Risk Reduction in Banda Aceh City. The aims of this research are to identify the participation and the contributions of women's organizations in Kota Banda Aceh and to define the strategies to strengthen women's organizations in Banda Aceh City in reducing the disaster risk. The design of this research is descriptive and qualitative by applying qualitative content analysis approach. Primary data is obtaining by conducted interviews with the representatives from women’s organization that become as the subject of this research, as well as secondary data is used by focus group discussion (FGD). The results of this study indicate that the form of participation of women's organizations are organizing, advocacy, campaigning, disaster mitigation education, aid raising and contracting public kitchen. The contribution of women's organizations in Banda Aceh City are to provide education, mentoring and fundraising. The strategies that should do by women’s organization is to build the synergies between the government and women's organizations to increase women capacity in the face of disaster.